Półka literacka 2010 - Agnieszka Nęcka (Postscriptum Polonistyczne)
The article presents the most important and the most interesting prose and poetic works published in 2010. Most of them were written by well known authors. The ones that particularly deserve mentioning are Balladyny i romanse by I. Karpowicz, Da capo by J. Franczak, Dziennik pisany później by A. Stasiuk, Spiski by W. Kuczok, Miasto Szklanych Słoni by M. Sieniewicz, Wąż w kaplicy by T. Piątek, Ziemia nod by R. Kobierski, Do rozpuku by A. Mirahina, Dywan by A. Wiedemann, Koncentrat by K. Siwczyk, Nocne życie by B. Zadura, poems by A. Sosnowski and Pół by M. Sendecki.